The Service Implications of a Rhetorical Approach to Information Literacy. - Brannon, Brittany (Public Services Quarterly)
Column description.TheFuture Voices in Public Servicescolumn is a forum for graduate students in library and information science programs to discuss key issues in academic library public services, to envision what they feel librarians in public service have to offer to academia, to tell us their visions for the profession, or to share research being conducted in library schools. We hope to provide fresh perspectives from those entering our field, in both the United States and other countries. Interested faculty of graduate library and information science programs, who would like their students’ ideas represented in these pages, are invited to contact Miriam L. Matteson. Brittany Brannon is an MLIS candidate in the School of Library and Information Science at Kent State University. In this essay, she makes an argument for incorporating a rhetorical approach when assisting students with their information seeking and use. A rhetorical approach focuses on how the student will use the information they seek, and thus emphasizes identifying the context, purpose, audience, situation, appeals, and genre required to complete the rhetorical act. Brannon argues that incorporating these ideas in reference and instruction service can help guide students as they seek, select, and evaluate information.